(untitled) (Journal of the College of Education for Women, 2023)
Narcissism is a complicated phenomenon that can be reflected in the narcissist’s language. Investigating narcissism in terms of linguistics, and pragmatics in particular, does not seem to have been given its due attention, as this study reveals. Thus, this study is an endeavor to discover how narcissism is reflected in the American movie Big Eyes (2014). It is known for introducing narcissistic behaviors. This paper aims to identify the types, motivations, and pragmatic manifestations of narcissism in the selected movie. Three pragmatic theories are chosen to scrutinize narcissism in the data: Searle’s speech acts (1969), Grice’s maxims breaching (1975), and Culppeper’s impoliteness (1996). To cope with the nature of the data and the aims of the study, an analytical framework that embraces three layers has been designed. These are the types, motivations, and pragmatic strategies of narcissism. Upon analyzing the data, the study concludes that exhibitionist narcissism abounds in the movie. In terms of motivations, environmental influence is the main factor behind narcissism in the data. Representative, directive and expressive speech acts appear in the data. The maxims have been breached to result in the use of metaphor and hyperbole. Four impoliteness strategies (positive, negative, bold on record, and mock impoliteness) are used to show narcissism in the data.